Mammal remains in Tyto furcata (Tytonidae: Strigiformes) pellets from Serra do Amolar, Mato Grosso do Sul - Marcus Vinicius Brandão (Caldasia, 2020)
Tyto furcata pellets provide important ecological data on its diet, as well as on the preyed mammals. The present study furnishes data on the diet of T. furcata in a Pantanal area, including records of rare mammals species and a variety of preys with different habits, furnishing evidence of the owl foraging areas.